Efficacy of sublingual and oral vitamin B12 versus intramuscular administration: insights from a systematic review and meta-analysis - Mazur, Marta; Ndokaj, Artnora; Salerno, Claudia; Vallone, Jessica; Ardan, Roman; Bietolini, Sabina; Carrouel, Florence; Wilk, Aleksandra; Sarig, Rachel; Ottolenghi, Livia; Bourgeois, Denis (Frontiers in Pharmacology, 2025)
BackgroundVitamin B12 deficiency is a widespread condition, particularly among elderly individuals, patients with malabsorption syndromes, and those following plant-based diets. This systematic review and meta-analysis aimed to evaluate and compare the effectiveness of sublingual and oral vitamin B12 administration in comparison with intramuscular (IM) injections, both for improving serum cobalamin and reducing homocysteine levels.MethodsA comprehensive search was conducted across PubMed, Scopus, and Embase up to July 2024. Eligible studies included randomised controlled trials, cohort, and case-control studies assessing B12 supplementation efficacy via oral, sublingual, or IM administration routes. Meta-analyses were performed using random-effects models. Subgroup analyses evaluated four key factors: administration route efficacy, daily dosage, age group and clinical conditions that may affect vitamin B12 metabolism (e.g., underlying pathology). Sixteen studies were included in the quantitative synthesis, comprising a total of 6,098 participants.ResultsVitamin B12 supplementation was associated with a significant increase in serum cobalamin levels across all routes of administration (pooled mean difference = +402.6 pg/mL; 95% CI: 293.6 to 511.5; p < 0.001). Homocysteine levels were also significantly reduced across all groups (pooled mean difference = −4.83 μmol/L; 95% CI: −6.55 to −3.11; p < 0.001). No statistically significant differences were observed between oral, sublingual, and intramuscular (IM) routes of administration (p = 0.270 for cobalamin levels and p = 0.485 for homocysteine levels), nor between randomised controlled trials and observational studies (p = 0.268 for cobalamin levels). No dose-response effect was observed (p = 0.485), suggesting that absorption efficiency rather than dosage may be the determining factor. Subgroup analyses by age and clinical conditions (e.g., gastrectomy, unspecified deficiency) revealed comparable efficacy across populations. However, heterogeneity was substantial (I2 > 80% in most comparisons), and Egger’s test indicated potential publication bias. Given the high heterogeneity, further studies are needed to confirm the results.ConclusionSublingual and oral B12 supplementation appear to be as effective as intramuscular (IM) injections in improving cobalamin status and reducing homocysteine levels. Given their non-invasive nature, accessibility, and cost-effectiveness of sublingual formulations, they may represent a promising approach for long-term B12 management, particularly in patients with impaired absorption or in resource-limited settings. Further high-quality RCTs are warranted to refine dosing strategies and confirm long-term outcomes.Systematic Review RegistrationCRD42024554513.